The diagnosis, isolation of etiological agents and antibiotic susceptibility test results in cows and buffalos suffering from subclinical mastitis - Erol ALAÇAM; Tevfik TEKELİ; Osman ERGANİŞ; A. Nedim İZGİ (Eurasian Journal of Veterinary Sciences)
In this study, diagnosis, isolation of microbiological agents and antibiotic susceptibility results were comparatively determined on sufoclinically mastitic cow's and buffalos in the same farm at differents seasons.